Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© Ø¹Ù† ÙƒØªØ§Ø¨ Ø§Ù„Ù†ØÙˆ Ù…Ù† Ø³Ù„Ø³Ù„Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ ÙˆÙ…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Mahmuddin, Ronny; Zulfiah Sam (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2021)
This research aims to know and describe a good textbook in teaching Arabic language skills, taking into account the teaching of grammatical rules to non-native speakers. As for the type of this research, it is qualitative descriptive research using the office method by analytical study on a textbook "The Grammar Book in the Arabic Language Teaching Series" with finding On resources to collect information. The results of this research indicated that the textbook in the grammar book in the series of teaching the Arabic language is a good textbook for teaching Arabic language skills, taking into account the teaching of grammar rules to non-native speakers, and the quality of this book is as follows: (For the first) this book uses the direct method in teaching Arabic language skills, taking into account the teaching of grammar rules to non-native speakers, (second) this book uses the audio-verbal method with a multiplication of mechanical exercises through listening and speaking, in order to form the habit of students while learning the grammar rules Through Alsaqq, (the third): This book uses the inductive method, which is the method that made the dialogic text the focus of language activities in speech or reading related to grammatical rules, with the use of the three language exercises based on the axial or reciting text, which are the (mechanical), semantic and communicative exercises, taking into account Theoretical grammar and (Fourth) Use the communicative method in teaching Arabic language skills, taking into account the teaching of grammar.